2018
DOI: 10.3324/haematol.2018.204701
|View full text |Cite
|
Sign up to set email alerts
|

Targeting intermediary metabolism enhances the efficacy of BH3 mimetic therapy in hematologic malignancies

Abstract: BH3 mimetics are novel targeted drugs with remarkable specificity, potency and enormous potential to improve cancer therapy. However, acquired resistance is an emerging problem. We report the rapid development of resistance in chronic lymphocytic leukemia cells isolated from patients exposed to increasing doses of navitoclax (ABT-263), a BH3 mimetic. To mimic such rapid development of chemoresistance, we developed simple resistance models to three different BH3 mimetics, targeting BCL-2 (ABT-199), BCL-X … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…Further, tigecycline also synergized with venetoclax in treatment of mice engrafted with DHL cell lines or patient derived xenografts [181]. Recent work by Al-Zebeeby et al, 2019, on identifying metabolic inhibitors that can target resistance mechanisms in CLL has shown that inhibition of glutamine uptake and metabolism by various inhibitors (transaminase inhibitor amino-oxyacetic acid (AOA), ASCT2 inhibitor GPNA, glutaminase inhibitor CB-839, and glutamine: fructose-6-phosphate-amidotransferase (GFAT) inhibitor Azaserine) was found to sensitize BCL-x L antagonist (A-1331852) resistant K562 cells to A-1331852 induced apoptosis [182]. Additionally, inhibition of downstream metabolic pathways such as reductive carboxylation, fatty acid synthesis and cholesterol synthesis by ATP-citrate lyase (ACLY) inhibitor SB20499, fatty acid synthase (FASN) inhibitor GSK2194069 and HMGCR inhibition by statins, respectively, sensitized resistant cells to A-1331852.…”
Section: Implications For Therapymentioning
confidence: 99%
“…Further, tigecycline also synergized with venetoclax in treatment of mice engrafted with DHL cell lines or patient derived xenografts [181]. Recent work by Al-Zebeeby et al, 2019, on identifying metabolic inhibitors that can target resistance mechanisms in CLL has shown that inhibition of glutamine uptake and metabolism by various inhibitors (transaminase inhibitor amino-oxyacetic acid (AOA), ASCT2 inhibitor GPNA, glutaminase inhibitor CB-839, and glutamine: fructose-6-phosphate-amidotransferase (GFAT) inhibitor Azaserine) was found to sensitize BCL-x L antagonist (A-1331852) resistant K562 cells to A-1331852 induced apoptosis [182]. Additionally, inhibition of downstream metabolic pathways such as reductive carboxylation, fatty acid synthesis and cholesterol synthesis by ATP-citrate lyase (ACLY) inhibitor SB20499, fatty acid synthase (FASN) inhibitor GSK2194069 and HMGCR inhibition by statins, respectively, sensitized resistant cells to A-1331852.…”
Section: Implications For Therapymentioning
confidence: 99%
“…Accordingly, targeting intermediary metabolism can be a novel strategy to enhance the efficacy of BH3 mimetics in hematologic malignancies. Thus, targeting glutamine uptake and its downstream signaling pathway, such as glutaminolysis, reductive carboxylation, lipogenesis, and cholesterogenesis, induced a marked sensitization of resistant cells to BH3 mimetics in CLL, MCL, and MM models [53]. In agreement, another preclinical study demonstrated that the combination of statins with venetoclax was cytotoxic to DLBCL, CLL, and AML cells and reduced lymphoma burden in a syngeneic mouse model of BCL-2/MYC driven "double hit" lymphoma [54].…”
Section: Venetoclax Resistance Due To Mitochondria Reprogramming and mentioning
confidence: 99%
“…Previously, we have reported that BH3 mimetics induce a novel paradigm of apoptosis characterised by marked ultrastructural changes in the mitochondria, involving the loss of mitochondrial cristae and the appearance of breaks in the OMM, resulting from mitochondrial matrix swelling 19,20,31 . In cell lines that depend for survival almost exclusively on BCL-2 (MAVER-1), BCL-X L -(K562) and MCL-1 (H929) 32 , exposure to the relevant BH3 mimetics, such as ABT-199, A-1331852 and A-1210477, respectively, resulted in similar mitochondrial matrix swelling and rupture of the OMM (Fig. 1a–c).…”
Section: Resultsmentioning
confidence: 97%